The Influence of Servant Leadership on Organization Culture, Organizational Commitment, Organizational Citizenship Behavior and Employees’ Performance (Study of Outstanding Cooperatives in East Java Province, Indonesia) - Harwiki, Wiwiek (Journal of Economics and Behavioral Studies, 2013)
The purposes of this research to investigate the influence of Servant Leadership to Organization Culture, Organizational Commitment, OCB and Employees’ Performance on Outstanding Cooperatives in East Java Province. Samples were collected amount 249 employees as unit samples. 30 managers as informant were asked to answer Employees’ Performance variable. Servant Leadership, Organization Culture, Organization Commitment and OCB variables were answered by employees. Structural Equal Modeling is used as a technique of analysis. The research findings: Servant Leadership influences to Organization Culture, Organizational Commitment, and Employees’ Performance significantly, but not to OCB; Organization Culture influences to OCB and Employees’ Performance significantly; Organizational Commitment influences to OCB significantly, but not to Employees’ Performance; OCB influences to Employees’ Performance significantly. The dominant indicators contribute to variables are: people orientation to Servant Leadership, power distance to Organization Culture, continuance commitment to Organizational Commitment, civic virtue to OCB, and individual attitude to Employees’ Performance. Servant Leadership encouraging employees easier, conducting their tasks better and building the organization values thus employees done their job well, honest and increasing their performance. Managers should be more empower themselves to help fellow workers help others voluntarily, fostering sportsmanship, altruism, conscientiousness, courtesy, and civic virtue of the employees.